Crime in Kharkiv and Its Counteraction in 1880 - V. A. Hrechenko; O. M. Honcharuk (Law and Safety)
There was a significant crime growth in the Russian Empire In 1880s in general and in particular on Ukrainian territory that was part of the Empire at that time. It was influenced by a set of reasons of political, social, organizational, economic and psychological nature, including the disintegration of the peasant community, the proletarianization of the peasants and their influx into the cities. The authors of this topic have considered two aspects of the problem: the history of crime prevention in the late XIX century, whose experience always remains relevant, and the history of Kharkiv of the same period, which is also interesting from a scientific point of view. The topic is insufficiently researched; the authors did not find publications where it would be specially researched. The researchers set out to reveal the main aspects of crime in Kharkiv in 1880s and some measures to combat it. This purpose is specified in the following tasks: to identify the main general factors in the crime growth in the country during this period; to consider some aspects of crime in Kharkiv that have not been studied so far: a) abuse at customs; b) the fight against alcoholism; c) combating prostitution. The authors for the first time in the historical and legal literature have studied the main aspects of crime in Kharkiv in 1880s, have highlighted the prehistory and the course of the resonant Kharkiv trial of 1885 on abuses at customs. The main directions of the fight against alcoholism have been revealed. The state of counteraction to prostitution in the city has been studied. The issue of the main reasons for the rapid growth of crime during that period has been supplemented. The authors have used the historical principle of research while writing of the article; processes, events and facts were studied in chronological order taking into account the socio-political situation of that time. The principle of objectivity, which the authors tried to adhere to, meant relying on the facts in their true meaning. Each historical and social phenomenon has been considered in its diversity and contradiction, in the aggregate of both positive and negative manifestations. The Kharkiv trial of 1885 demonstrated the shortcomings of the Judicial Reform of 1864, the activities of lawyers and the jury. Counteracting alcoholism and prostitution in the city was formal and ineffective. The operation of whorehouses was regulated by the state, which understood its task only in combating the spread of sexually transmitted diseases and combating mischief in the locations of whorehouses. The materials of the article can be used while teaching the disciplines “History of State and Law of Ukraine”, “History and Culture of Ukraine”, special course “History of Law Enforcement Agencies of Ukraine”, for writing monographs on the history of law enforcement agencies, the history of Kharkiv.